On the Application of Argument Accrual to Reasoning with Inconsistent Possibilistic Ontologies - Gómez, Sergio Alejandro (2016)
We present an approach for performing instance checking in a suitable subset of possibilistic description logic programming ontologies by using argument accrual. Ontologies are interpreted in possibilistic logic programming under Dung's grounded semantics. We present a reasoning framework with a case study and a Java-based implementation for enacting the proposed approach.